Firm Size and Leverage on Company Performance : The Role of IT Investment as a Moderation Variable - Andika Putri, Indah; Yolandafitri Zulvia (International Journal of Economics and Management Research, 2025)
This study aims to analyze the effect of firm size and leverage on company performance with Information Technology Investment (ITI) as a moderating variable in non-primary consumer goods sector companies (consumer cylicals) listed on the Indonesia Stock Exchange in 2021-2023. The population in this study were all non-primary consumer goods sector companies (consumer cylicals) listed on the Indonesia Stock Exchange. The sample in this study was 85 companies with 220 observation data obtained using purposive sampling techniques. This study uses multiple linear regression analysis methods and Moderated Regression Analysis (MRA) using IBM SPSS 30 software. The results of this study conclude that firm size has a significant positive effect on company performance, leverage has a significant negative effect on company performance, Information Technology Investment (ITI) significantly strengthens the effect of firm size on company performance, Information Technology Investment (ITI) does not moderate the relationship between leverage and company.